The Role of Zakat, Waqf, and Islamic Business in Sustainable Economic Development: A Review of Funding and Fund Provision Models - Siti Nurhaliza; Seli Sukma Anggraini; Febi Bonita; Dini Imeliani; Melati Luniagus; Muhammad Nafiscal Farih (Journal of Economics and Business, 2025)
This research aims to determine and comprehen about zakat and waqf role in the economic development of the Muslims (Ummah) in Islamic economic perspective. Research types is library research. Research approach using combination of a philosophical and phenomenological approach. A philosophical approach is used to look deeply at philosophical material objects such as values, principles, Islamic economic goals and zakat and wakaf role in Muslims (ummah) economic development. While the phenomenological approach is used to look at the economic development that is reflected in society through statistical data about poverty, as well as those contained in a literature work such as books, documents, scientific works and research. Study result: Islamic economic system aims is to improve society welfare and to realize maqasid as sharia, and uphold justice value, therefore the important base of zakat and waqf distribution is Allah guidance in Qur’an Surah (chapter) [59]: 7  " so that the wealth should not circulate among the rich people among you... "from these foundation spawned a great concept of zakat and waqf role in economic development. Zakat and waqf are economic development instruments. Empowerment and management of coordinatively between government and society make a positive contribution in Muslims economic development.   ABSTRAK   Penelitian ini bertujuan untuk menggali peran zakat dan wakaf dalam pembangunan ekonomi umat perspektif ekonomi Islam. Penelitian ini merupakan penelitian kepustakaan (Library Research}, dengan pendekatan kombinasi dari pendekatan filosofis dan fenomenologis. Pendekatan filosofis digunakan untuk melihat secara mendalam objek material filsafat seperti nilai, prinsip, tujuan ekonomi Islam juga peran zakat dan wakat dalam pembangunan ekonomi umat. Sedangka pendekatan fenomenologis dipakai untuk melihat pembangunan ekonomi yang tergambar di masyarakat melalui data-data kemiskin yang ada, hal-hal yang tertuang dalam karya ilmiyah, dekumen, dan hasil-hasil penelitian. Hasil yang didapatkan dari penelitian ini bahwa tujuan sistem ekonomi Islam adalah untuk menyejahterakan masyarakat, mewujudkan maqasid as syariah, menjunjung tinggi nilai keadilan, sehingga pada level distribusi zakat dan wakaf, harus berpedoman pada petunjuk Allah dalam Qs.[59]: 7         ” agar harta itu jangan hanya beredar di antara orang-orang kaya saja diantara kamu ..” Dari acuan tersebut melahirkan sebuah konsep bahwa peran zakat dan wakaf dalam pembangunan ekonomi umat sangat besar. Zakat dan wakaf merupakan salah satu instrumen pembangunan ekonomi. Pengelolaan serta pemberdayaan zakat dan wakaf dengan baik oleh pemerintah bersama masyarakat secara koordinatif, berkontribusi positif dalam pembangunan ekonomi umat